Multinationality, R&D and productivity: Evidence from the top R&D investors worldwide. Issue 3 (June 2017) - Castellani, Davide; Montresor, Sandro; Schubert, Torben; Vezzani, Antonio
Highlights: The relationship between multinationality and productivity is reconceptualised. Multinational breadth and depth affect productivity directly and indirectly, via R&D. An empirical application to top R&D spenders worldwide confirms these effect differ. Multinational depth and breadth augment R&D, but only depth increases productivity. Abstract: This paper investigates the effects of multinationality on firm productivity, and contributes to the literature in two respects. First, we argue that multinationality affects productivity both directly and indirectly through higher incentives to invest in R&D. Second, we maintain that the multinational depth and breadth have different direct effects on productivity and R&D. Using data from the top R&D investors in the world, we propose an econometric model with an R&D and a productivity equation that both depend on multinationality. We find: i) multinational depth has a positive effect on productivity, while the effect of multinational breadth is negative; ii) multinationality (along both dimensions) has a positive effect on R&D intensity, translating into an indirect positive effect on productivity; iii) the positive indirect effect is however not large enough to compensate the negative direct effect of multinational breadth.